Superradical Hysterectomy for Cervical Cancer as an Alternative to the Usual Okabayashi-Type Radical Hysterectomy - Mandai, Masaki; Yamaguchi, Ken; Hamanishi, Junzo; Sekiyama, Kentaro; Kondoh, Eiji (The Surgery Journal, 2021)
Radical hysterectomy is a standard operation for invasive cervical cancers. However, if the invasion to the parametrium is more advanced than estimation in the operation, it is difficult to perform usual radical hysterectomy. Superradical hysterectomy was developed by Prof. Ryukichi Mibayashi of Kyoto University and was published in 1941, and has been performed for the limited cases by a part of Japanese gynecologic surgeons. Superradical hysterectomy is a procedure in which the soft tissues in the pelvis are removed en bloc by sequential processing of the internal iliac vessels, which leads to a complete dissection of the lymphatic tissue in the pelvis to the pelvic wall.
Keywords: superradical hysterectomy; cervical cancer; internal iliac vessels; locally advanced; Mibayashi